Anticipation of a mentally effortful task recruits Dorsolateral Prefrontal Cortex: An fNIRS validation study. (4th February 2019) - Vassena, Eliana; Gerrits, Robin; Demanet, Jelle; Verguts, Tom; Siugzdaite, Roma
Abstract: Preparing for a mentally demanding task calls upon cognitive and motivational resources. The underlying neural implementation of these mechanisms is receiving growing attention because of its implications for professional, social, and medical contexts. While several fMRI studies converge in assigning a crucial role to a cortico-subcortical network including Anterior Cigulate Cortex (ACC) and striatum, the involvement of Dorsolateral Prefrontal Cortex (DLPFC) during mental effort anticipation has yet to be replicated. This study was designed to target DLPFC contribution to anticipation of a difficult task using functional Near Infrared Spectroscopy (fNIRS), as a more cost-effective tool measuring cortical hemodynamics. We adapted a validated mental effort task, where participants performed easy and difficult mental calculation, and measured DLPFC activity during the anticipation phase. As hypothesized, DLPFC activity increased during anticipation of a hard task as compared to an easy task. Besides replicating previous fMRI work, these results establish fNIRS as an effective tool to investigate cortical contributions to anticipation of effortful behavior. This is especially useful if one requires testing large samples (e.g., to target individual differences), populations with contraindication for functional MRI (e.g., infants or patients with metal implants), or subjects in more naturalistic environments (e.g., work or sport). Highlights: Anticipating a mentally effortful task recruits DLPFC, measured by fMRI. fNIRS is a cost-effective method to measure cortical activity (oxyhemoglobin). This study validates the use of fNIRS to measure difficulty anticipation in DLPFC. Anticipating a hard task is associated with increased oxyhemoglobin in DLPFC. fNIRS can be used in studies investigating the role of DLPFC in mental effort.